2022
DOI: 10.1021/acs.biochem.2c00364
|View full text |Cite
|
Sign up to set email alerts
|

C3- and C3/C5-Epimerases Required for the Biosynthesis of the Capsular Polysaccharides from Campylobacter jejuni

Abstract: Campylobacter jejuni is a human pathogen and one of the leading causes of food poisoning in Europe and the United States. The outside of the bacterium is coated with a capsular polysaccharide that assists in the evasion of the host immune system. Many of the serotyped strains of C. jejuni contain a 6-deoxy-heptose moiety that is biosynthesized from GDP-D-glycero-D-mannoheptose by the successive actions of a 4,6-dehydratase, a C3/C5-epimerase, and a C4-reductase. We identified 18 different C3/C5epimerases that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…The steady-state concentration of the specific substrate for the C4-reductase was calculated from the known equilibrium constants for the action of the epimerase with GDP-6-deoxy-4-keto- d - lyxo -heptose (see Figure ). The kinetic constants are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steady-state concentration of the specific substrate for the C4-reductase was calculated from the known equilibrium constants for the action of the epimerase with GDP-6-deoxy-4-keto- d - lyxo -heptose (see Figure ). The kinetic constants are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
“…11 The predicted products for the HS:10A and HS:10B C4-reductases are GDP-6-deoxy-α-D-altro-heptose (3) and GDP-6-deoxy-β-L-galactoheptose (7), respectively, and thus, the HS:10B reductase is the one that was apparently expressed for the specific strain that was used for those investigations. This is interesting since the epimerase identified in the HS:10 serotype (UniProt id: F2X784) is likely restricted to the epimerization of only C3, 31 and thus, it is uncertain how C5 is epimerized for the ultimate formation of GDP-6-deoxy-β-L-galacto-heptose (7). For serotype HS:41, the reported heptose is 6-deoxy-D-altroheptose, 11 and the predicted products for the HS:41A and HS:41B C4-reductases are GDP-6-deoxy-D-altro-heptose and GDP-6-deoxy-L-galacto-heptose, respectively, and thus, the HS:41A C4-reductase was apparently expressed for the specific strain that was used for those investigations.…”
Section: ■ Discussionmentioning
confidence: 99%
“…11,15,16 analysis of the DNA-sequenced serotypes of C. jejuni has demonstrated that there is a single common 4,6-dehydratase, 9 but two types of epimerases are utilized for the biosynthesis of the 6-deoxy-heptoses. 10 We have demonstrated that the largest class of epimerases (from serotypes HS:3, HS:4, HS:8, HS:10, HS:12, HS:23/36, HS:29, HS:33, and HS:41) is limited to the epimerization of C3, whereas the second-most populated class of epimerases (from serotypes HS:2, HS:15, HS:32, HS:42, and HS:63) catalyzes the racemization of C3 and C5. 10 For the eight C4-reductases that have been functionally characterized to date (serotypes HS:2, HS:3, HS:4, HS:15, HS:23/36, HS:33, HS:42, and HS:53), the epimerase in the gene cluster of that serotype is a C3/C5-epimerase if C5 is epimerized but is a C3-epimerase if C5 is not epimerized in the final 6-deoxy heptose product.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10 We have demonstrated that the largest class of epimerases (from serotypes HS:3, HS:4, HS:8, HS:10, HS:12, HS:23/36, HS:29, HS:33, and HS:41) is limited to the epimerization of C3, whereas the second-most populated class of epimerases (from serotypes HS:2, HS:15, HS:32, HS:42, and HS:63) catalyzes the racemization of C3 and C5. 10 For the eight C4-reductases that have been functionally characterized to date (serotypes HS:2, HS:3, HS:4, HS:15, HS:23/36, HS:33, HS:42, and HS:53), the epimerase in the gene cluster of that serotype is a C3/C5-epimerase if C5 is epimerized but is a C3-epimerase if C5 is not epimerized in the final 6-deoxy heptose product. 11 However, for some serotypes (namely, HS:8, HS:10, HS:29, HS:41, and HS:63), there are two nonredundant C4-reductases in the gene cluster.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation